2017
DOI: 10.1167/iovs.16-20505
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Chromatic Pupillography Protocol for the First Gene Therapy Trial in Patients With CNGA3-Linked Achromatopsia

Abstract: Citation: Lisowska J, Lisowski L, Kelbsch C, et al. Development of a chromatic pupillography protocol for the first gene therapy trial in patients with CNGA3-linked achromatopsia. Invest Ophthalmol Vis Sci. 2017;58:127458: -128258: . DOI:10.1167 PURPOSE. To establish a feasible and sensitive pupillographic protocol to assess outer and inner retinal function for the first gene therapy trial in achromatopsia patients (ACHM) with mutations in CNGA3.METHODS. Twenty-seven CNGA3-ACHM patients and 22 age-matched con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…For a reliable interpretation of the data and to facilitate replication of findings, the absolute pupil baseline diameter before the stimulation should be reported. This metric varies widely across participants with a characteristic decreasing pupil size with age (2) and hints for smaller pupil sizes in specific retinal diseases, e.g., in CNGA3-linked Achromatopsia (35). Further analyses should usually be based on relative values as pupillary responses are dependent on the initial baseline diameter, which should be obtained during a sufficiently long recording period to ensure a steady and reliable estimate.…”
Section: Part: General Standards For Pupillographymentioning
confidence: 99%
See 2 more Smart Citations
“…For a reliable interpretation of the data and to facilitate replication of findings, the absolute pupil baseline diameter before the stimulation should be reported. This metric varies widely across participants with a characteristic decreasing pupil size with age (2) and hints for smaller pupil sizes in specific retinal diseases, e.g., in CNGA3-linked Achromatopsia (35). Further analyses should usually be based on relative values as pupillary responses are dependent on the initial baseline diameter, which should be obtained during a sufficiently long recording period to ensure a steady and reliable estimate.…”
Section: Part: General Standards For Pupillographymentioning
confidence: 99%
“…There are examples of chromatic pupillometry methodologies that provide initial efforts to separate rod and cone function through the careful control of the wavelength, irradiance, size and duration of the test stimuli; the degree of separation of rod and cone (and melanopsin) function that these conditions provide is still to be determined. At light levels below cone threshold, short wavelength lights are presented in the dark to bias the response to rods, with the PIPR amplitudes minimized under such conditions (9, 11, 35). To ensure maximal rod sensitivity, the pre-stimulus dark adaptation time should be at least 30 min (91); although this is not practical for all clinical protocols, shorter periods will influence the relative rod and cone sensitivity to the test stimuli.…”
Section: The Afferent Pupillary Pathway Authors: Carina Kelbsch Amentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these and subsequent studies showed that the PLR for chromatic light may potentially be used for diagnosis and monitoring disease progression as well as determination of treatment efficacy and safety in retinal and optic nerve diseases. 5,[7][8][9][10][13][14][15][16] Recently, Park et al 17 characterized the PLR mediated by the different photoreceptor classes when using smaller stimulus sizes presented in the center of the visual field (VF) over a large range of light intensities. Chibel et al 18 provided evidence that the function of rods and cones at different locations in the central (16.28) VF can be assessed using smaller (Goldmann size III, 0.438) red and blue light stimuli at 1000 and 200 cd/m 2 , respectively, under mesopic (0.05 cd/m 2 uniform white light) adaptation.…”
mentioning
confidence: 99%
“…Stimulus projection was achieved with a time-triggered Espion Ganzfeld ColorDome Stimulator (Espion E 2 ; Diagnosys LLC, Lowell, MA, USA). Based on the protocols described by Park et al, 23 Kardon et al, 24 Kawasaki et al, 25 and Lisowska et al, 26 blue and red stimuli were displayed with a duration of 1 second under darkand light-adapted conditions. All preterm-born and term-born children were tested with a protocol containing three repeats of fixed illuminances (0.01 cd/m 2 blue stimuli at a wavelength of 460 nm and 100 cd/m 2 red stimuli at a wavelength of 640 nm).…”
Section: Optical Coherence Tomography and Layer Segmentationmentioning
confidence: 99%